JENIS DAN POPULASI SERANGGA HAMA PADA BERAS DI GUDANG TRADISIONAL DAN MODERN DI PROVINSI GORONTALO - Ilato, Jems; Dien, Moulwy F.; Rante, Caroulus S. (EUGENIA, 2012)
ABSTRACT The quality and quantity of rice as a source of food for most of Indonesian people are closely connected with the activity of insect pests in Warehouse. This study aims to determine the species and insect pests populations on Rice at Traditional and Modern Warehouse in Province of Gorontalo. The study used a survey method shelter/rice warehouse in Mootilango district, Boliohuto District, and Tolangohula district, Gorontalo province. Sampling was conducted in a purposive sampling is to take a sample of the suspected rice pests. Sampling was carried out 4 times with a time interval of 2 weeks. The research found six species of insect pests on rice commodities in Gorontalo regency consisting of 5 species of the order Coleoptera and 1 type of the order Lepidoptera. The results show that the identification of insect pests found are Sitophilus oryzae (Coleoptera; Curculionidae), Tribolium castaneum (Coleoptera: Tenebrionidae), Carpophilus hemipterus (Coleoptera: Nitidulidae) Oryzaephilus sp. (Coleoptera; Silvanidae), Ahasverus sp. (Coleoptera; Cucujidae), Corcyra cephalonica (Lepidoptera; Pyralidae). Average highest pest insect populations, respectively S. oryzae (54.60 individuals), Tribolium sp. (13.85 individuals), Oryzaephilus sp. (4.52 individuals), Ahasverus sp. (3.42 individuals), Corcyra sp. (2.42 individuals) and C. hemipterus (6.94 individuals), while the highest populations of insect pests found in traditional 16.40 modern warehouses 12.34 individual Keywords : insect pests, rice, traditional and modern werehouse